Produksi Bahan Bakar Minyakbio (Bio Oil) dari Sampah Kota Bandar Lampung dengan Metode Pirolisis Sebagai Solusi Terbaik dalam Manajemen Pengelolaan Sampah dan Diversifikasi Energi - Ali Mustofa; Indra Mamad Gandidi; Andicha Aulia Putra; Reno Raines (Balitbangda Provinsi Lampung, 2017)
The waste load produced by the community of Bandar Lampung city was 3.083 m3 per day or equivalent to 688 tons/day of wet waste with moisture content of approximately 60 %. In its management, the City Government of Bandar Lampung was using open dumping practices that were no longer relevant. On the other hand, waste was known to have stored energy in the form of chemical bonds between carbon molecules, hydrogen and oxygen molecules. When chemical bonds disrupted, the waste released chemical energy in the form of gases, liquids and solids commonly called biofuel. The research done using Bandar Lampung city wastes with pyrolysis technique producedliquid fuel with quality above diesel oil and below premium with yield or rendementabout 20.4%. Of the total drywaste 344 ton/day, Bandar Lampung citycouldproduce liquid fuel (bio-oil) around 68.8 ton/day or equal to 86.000 l/day. If it was assumed that the price of pyrolytic liquid fuel was Rp3000/l, then the return could be about Rp258000000/day. The financial calculations in this study indicated that if the pyrolysis machine is operated at the kelurahan level, the BEP was achieved within 8.5 months.